Comparison of the Transcriptome of the Ovine Mammary Gland in Lactating and Non-lactating Small-Tailed Han Sheep - Wang, Jiqing; Zhou, Huitong; Hickford, Jon G. H.; Hao, Zhiyun; Shen, Jiyuan; Luo, Yuzhu; Hu, Jiang; Liu, Xiu; Li, Shaobin (Frontiers in Genetics, 2020)
Small-Tailed Han (STH) sheep are known for their high fecundity, but the survival of lambs is compromised and influences the commercial return from farming these sheep, with this being attributed in part to starvation from insufficient milk production by the ewes. In this study, the transcriptome profiles of the mammary gland of lactating and non-lactating STH ewes were investigated using paired-end RNA sequencing (RNA-Seq). An average of 14,447 genes were found to be expressed at peak-lactation in the STH sheep, while 15,146 genes were expressed in non-lactating ewes. A total of 4,003 differentially expressed genes (DEGs) were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that the DEGs were associated with a wide range of cellular components, biological processes and metabolic pathways, including binding activities, signalling pathways, cellular structures, and immune responses. The most highly expressed genes at peak-lactation included CSN2, LGB, LALBA, CSN1S1, CSN1S2, and CSN3, and the 10 most highly expressed genes accounted for 61.37% of the total Reads Per Kilobase of transcript, per Million mapped reads (RPKM). The most highly expressed genes in the mammary gland of non-lactating ewes included IgG, THYMB4X, EEF1A1, IgA, and APOE, and the 10 most highly expressed genes accounted for only 12.97% of the total gene RPKM values. This suggests that the sheep mammary gland undergoes a substantial development in milk protein synthesis infrastructure and promotion of protein transportation during lactation.